Final instar larvae of Argia mollis Hagen in Selys, 1865 and Argia smithiana Calvert, 1909 (Odonata: Coenagrionidae) from the Brazilian Cerrado - Cezário, Rodrigo Roucourt; Vilela, Diogo Silva; Guillermo-Ferreira, Rhainer (Zootaxa, 2018)
Recent expeditions to the Serra da Canastra and Chapada dos Guimarães National Parks in Brazil resulted in the collection of larvae of Argia mollis Hagen in Selys, 1865 and A. smithiana Calvert, 1909. Thus, here we describe the last instar larvae of these two Argia species from the Brazilian Cerrado.